2021
DOI: 10.2147/idr.s295257
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Mastitis and Isolation, Identification and Antibiogram of Staphylococcus Species from Mastitis Positive Zebu Cows in Toke Kutaye, Cheliya, and Dendi Districts, West Shewa Zone, Oromia, Ethiopia

Abstract: Purpose Mastitis is one of the major global problems severely affecting the dairy sector. Staphylococcus species are the primary bacteria consistently identified from mastitic milk. This study was aimed to estimate the prevalence of mastitis, isolate Staphylococcus species, determine risk factors, and the antimicrobial susceptibility profile of Staphylococcus species from mastitic Zebu cows in West Shewa Zone, Ethiopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
3
22
3
Order By: Relevance
“…The present study results, however, were much higher than the result of Dabele et al 7 3.2% in selected districts of West Shewa Zone, Oromia, Ethiopia, Bedacha and Menghistu, 35 5.3% (15/278) in Batu districts, Bitew et al 38 3% (9/302), Moges et al 44 in the Gondar district by 0.93% (3/322) and Dabash et al 18 8.3% (12/144). This variance in mastitis prevalence between studies might indicate that the illness is complicated, interacting with a number of factors, including management methods, husbandry systems, the environment, causal factors, veterinary service coverage, and a lack of intermammary infusion.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…The present study results, however, were much higher than the result of Dabele et al 7 3.2% in selected districts of West Shewa Zone, Oromia, Ethiopia, Bedacha and Menghistu, 35 5.3% (15/278) in Batu districts, Bitew et al 38 3% (9/302), Moges et al 44 in the Gondar district by 0.93% (3/322) and Dabash et al 18 8.3% (12/144). This variance in mastitis prevalence between studies might indicate that the illness is complicated, interacting with a number of factors, including management methods, husbandry systems, the environment, causal factors, veterinary service coverage, and a lack of intermammary infusion.…”
Section: Discussioncontrasting
confidence: 95%
“…This finding was higher than the outcome of Zeryehun and Abera, 9 51.8% (199/247) in the Eastern Harrarghe zone, Tuke et al 12 51.44% (71/138) in Alage dairy farm, Zeryehun et al 28 55.1% (275/373) in Addis Ababa, Bedane et al, 34 38.8% (175/460) in Asella, and Mekibib et al, 13 44.6% (52/107) in Holeta district, Workineh et al 42 38.2% (71/186) from two major Ethiopian dairies. The results of this research were far higher than the outcomes of Bedacha and Menghistu, 35 40.6% (113/278) in Batu district, Belina et al, 20 40.7% (192/471) in North Shewa, and Borana pastoral area, Sori et al 43 36.67% (66/180) in Sebeta district, Moges et al, 44 31.67% (102/322) in Gondar district, Dabele et al 7 27.2% in three districts of West Shewa Zone, Bitew et al 38 25.2% (76/302) in Bahir Dar districts, and Kitila et al 17 22.7% in west Wollega, western Oromia, Ethiopia and lower than the findings of Dabash et al, 18 who found 80.6% (116/144) in North Shewa zone of Ethiopia.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…1 It is a kind of topical inflammation reaction, mainly due to the invasion of mammary gland tissue by microorganism. 2,3 S. dysgalactiae has become the major cause behind several mammalian infections, which can lead to streptococcal mastitis/endometritis in domestic mammals and skin lesions, meningitis, and bacteremia in humans. 4 In Swedish and other countries, it is recognized as the most common causative pathogens of bovine mastitis.…”
Section: Introductionmentioning
confidence: 99%